Dialog med fortiden – eller nutiden? Om P.G. Lindhardts og Hal Kochs historiebrug - Reeh, Tine Ravnsted-Larsen (Kirkehistoriske Samlinger, 2014)
Summary Hal Koch (1904-1963) and P.G. Lindhardt (1910-1988) were influential theologians in 20th century Denmark and they both chose church history as their line of work. Both were students of J. Oskar Andersen, who introduced historical criticism into the field of Danish church history, and in their studies they continued Andersen’s views on the necessity of strictly scientific standards within churchhistoriography. This position led to conflict with numerous groups within the church with Christian Bartholdy as one of the most prominent opponents. Despite the strong opposition the position of Koch and Lindhardt prevailed. Even though the two shared scientific historiography as a point of departure they were divided on the question whether church history could be considered theology. For Koch historical studies had a hermeneutic and a critical potential and as such they were able to contribute to contemporary theology when their hermeneutical or critical fruits had theological relevance. As a consequence of Koch’s hermeneutical approach, historical studies provide a possibility of some sort of dialogue with the historical material. In contrast, Lindhardt dismissed the existence of theology and the value of speculations on God, and he opposed Koch’s talk of dialogue with the past. Nevertheless Koch argued that Lindhardt’s own works were an example of a theological dialogue with the past. Regardless of their different views on dialogue with the historical material they both used their work with past as a powerful resource in the debates on church and Christianity in their own time.